Effect of Hydrogen Inhalation Therapy on Hearing Loss of Patients With Nasopharyngeal Carcinoma After Radiotherapy - Kong, Xiaofeng; Lu, Tianyu; Lu, You-Yong; Yin, Zhinan; Xu, Kecheng (Frontiers in Medicine, 2022)
Objective To evaluate the clinical efficacy and safety of hydrogen inhalation in improving hearing loss in patients with long-term survival of nasopharyngeal carcinoma after radiotherapy. Methods The eustachian tube dysfunction score, pure tone air conduction threshold, bone conduction threshold, the score of tympanogram and otoscope were prospectively observed in patients with deafness after radiotherapy only or combined radiotherapy and chemotherapy for nasopharyngeal carcinoma. Paired t test and one-way analysis of variance were used to analyze the data before and after treatment. Results A total of 17 patients were observed. The median time from radiotherapy to now was 228 months, and the median time from the diagnose of deafness to now was 92 months. After 4 weeks of hydrogen inhalation, the score of eustachian tube dysfunction, air conduction and bone conduction hearing thresholds were significantly reduced, P values were 0.0293, 0.0027, 0.0404, respectively. The mean air-bone gap, the score of otoendoscopy and tympanogram were also decreased, but the differences were not significant(P=0.2079,P=0.0536,P=0.1056). Patients with radiotherapy alone and concurrent chemo-radiotherapy had significantly lower air conduction hearing threshold after hydrogen absorption(P=0.0142,P=0.0495). The results of air and bone hearing thresholds before, 4 and 12 weeks after hydrogen inhalation showed a descending trend. The air and bone hearing thresholds before hydrogen inhalation were 74.69±27.03dB and 45.70±21.58dB, respectively. At the 12th week, the mean values of air and bone hearing thresholds were the lowest, which were 66.88±20.88 dB and 40.94±18.93 dB, respectively, but there was no significant difference in air and bone hearing thresholds among all groups (P=0.6755,P=0.7712). After hydrogen inhalation treatment, no adverse reactions such as nosebleed, chest pain, dyspnea, nausea, vomiting, dizziness, earache and allergic reaction were observed. Conclusion This is the first prospective study on the effect of hydrogen inhalation on hearing improvement in patients with deafness after radiotherapy/chemotherapy for nasopharyngeal carcinoma, suggesting that continuous hydrogen inhalation may be an alternative rehabilitation therapy for these patients.